Low sensitivity of F-wave in the electrodiagnosis of carpal tunnel syndrome. Issue 2 (April 2015) - Mondelli, Mauro; Aretini, Alessandro
Abstract Objective Previous studies showed "F-wave inversion" (F-INV) as a sensitive method in the electrodiagnosis of early stage of carpal tunnel syndrome (CTS). This study aimed at evaluating the sensitivity and specificity of F-wave and nerve conduction velocity (NCV) testing in CTS. Methods We consecutively enrolled 244 cases and 108 controls. F-waves analysis included: Fwave minimum and mean latencies, F-wave persistence and chronodispersion, mean-F/CMAP amplitude ratio, F-INV. Specificity and sensitivity of F-waves parameters were calculated in the whole sample of CTS patients and by grouping the patients according to CTS severity. Multivariate logistic regression was also performed using F-INV as a dependent variable. Results In the whole sample the sensitivity of F-mean-INV and of median–ulnar NCV comparative testing was 50.8% and 93.7%, respectively. F-INV sensitivity dropped to 8% in CTS early stage. F-INV could be predicted only by distal motor latency of the median nerve. The sensitivity of all F-wave parameters increased only in the most severe stages of CTS. Conclusions This study does not confirm the electrodiagnostic usefulness of F-INV in early stage of CTS. All F-wave parameters, including F-INV, are much less sensitive than conventional NCV in CTS electrodiagnosis. F-wave does not add further useful information specifically related to CTS.